1988
DOI: 10.1111/j.1439-0523.1988.tb00213.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Genetic Relationship between Anther Culture and Somatic Tissue Culture Abilities in Wheat

Abstract: A population of thirty-eight doubled haploid lines, developed from the F, between Vfro wheat parents differing m anther culture and somatic tissue culture responses, was used to examine the genetical control of re'sponses to these m vitro systems.During anther culture genetic variation between hnes ' was exhibited for frequencies of callus induction, embryo production and embryo regeneration rates. In addition the relative frequencies of green and albino plants ' was shown to be genotype dependent. Hoivever, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0
2

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 18 publications
5
14
0
2
Order By: Relevance
“…However, a high frequency of androgenetic embryoids is not necessarily associated with a high frequency of regenerated plantlets . Similar results have been observed in anther culture Wenzel & Uhrig, 1981 ;Cappadocia et al ., 1984 ;Agache et al ., 1988) . Because no positive correlation between frequency of responding anthers and frequency of embryoids regenerating into plantlets was observed, androgenetic competence and regeneration may be under independent genetic control .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a high frequency of androgenetic embryoids is not necessarily associated with a high frequency of regenerated plantlets . Similar results have been observed in anther culture Wenzel & Uhrig, 1981 ;Cappadocia et al ., 1984 ;Agache et al ., 1988) . Because no positive correlation between frequency of responding anthers and frequency of embryoids regenerating into plantlets was observed, androgenetic competence and regeneration may be under independent genetic control .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, selection for each character has to be considered independently . Similar results have been found for callus growth and shoot regeneration in tomato (Koornneef et al ., 1987) and anther culture and somatic tissue culture of wheat (Agache et al ., 1988). However, the genes for regeneration of embryoids can act only in the presence of androgenetic genes .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, genes increasing somatic embryo induction frequency, regeneration ability and albino frequency have been located on the wheat chromosomes (Henry & De Buyser, 1985 ;Agache et al ., 1989) . Genotypic effects have also been reported for wheat somatic tissue culture capacity (Mathias & Simpson, 1986 ;Rode et al ., 1988), It has also been demonstrated that there was no correlation between the performance of lines in anther culture and somatic tissue culture, indicating separate genetic control of responses of these tissues (Agache et al ., 1988) . Thus a considerable body of evidence now indicates that regeneration of wheat plants from tissue cultures is under genetic control, but the information on the genetic control of regeneration is restricted (Agache et al ., 1988 ;Felsenburg et al ., 1987 ;Galiba et al ., 1986 ;Henry & De Buyser, 1985 ;Ou et al ., 1989) .…”
Section: Introductionmentioning
confidence: 99%
“…This case may cause to reduce albino by the control of culture conditions. Agache et al (1988) showed that all three androgenic traits inherited dependently. Dominant and additive genes that affect on these traits may cause to convert important cultivars with low response into cultivars with high response to androgenesis.…”
Section: The Effect Of Cultivarmentioning
confidence: 99%
“…culture of hexaploid wheat, embryo induction, total plant regeneration and green plant regeneration inherited independently (Agache et al, 1988). This fitness provides the basis for introducing these traits into genotypes with low response.…”
mentioning
confidence: 99%